Teixobactin as a scaffold for unlimited new antimicrobial peptides: SAR study. Issue 10 (1st June 2018) - Abdel Monaim, Shimaa A.H.; Jad, Yahya E.; El-Faham, Ayman; de la Torre, Beatriz G.; Albericio, Fernando
Graphical abstract: Abstract: It looks that a new era of antimicrobial peptides (AMPs) started with the discovery of teixobactin, which is a "head to side-chain" cyclodepsipeptide. It was isolated from a soil gram-negative b-proteobacteria by means of a revolutionary technique. Since there, several groups have developed synthetic strategies for efficient synthesis of this peptide and its analogues as well. Herein, all chemistries reported as well as the biological activity of the analogues are analyzed. Finally, some inputs regarding new trends for the next generation of analogues are discussed.